Exploring Students’ Motivation in Learning English at English Laboratory of UBL - Sari Ayu, Eka; Dwi Prastyo, Yanuar (Al Makki Publisher, 2025)
Motivation is an important factor in language learning, including English. Without motivation, a person will lose the spirit of learning which can affect their success. This study aims to determine the level of motivation of students in learning English and determine the type of motivation that is more dominant, namely intrinsic or extrinsic motivation. This study used descriptive qualitative method with instruments in the form of questionnaires and interviews. The research participants were 192 third-semester students studying at the language laboratory of Bandar Lampung University. The data were analyzed using a five-point Likert scale to measure the overall level of motivation and compare intrinsic and extrinsic motivation. The results showed that most students had a high level of motivation in learning English, with an average score of 4.26. The dominant motivation found was intrinsic motivation, with an average score of 4.26, compared to extrinsic motivation which had a score of 3.94. Students are more motivated to learn English for personal reasons such as interest in the English language and culture as well as the desire to improve communication skills. In conclusion, intrinsic motivation is more dominant than extrinsic motivation in learning English at the language laboratory of Bandar Lampung University. Therefore, it is recommended that teachers continue to support and enrich learning methods that can increase students' intrinsic motivation.